ANALISIS PERAWATAN PERENCANAAN PHASE 25 DI BATAM AERO TECHNIC (BAT) SM-SUB - Rakahila, Raihan Aventa; Rahmawati, Fajar Khanif (Institut Teknologi Dirgantara Adisutjipto, 2023)
Airplanes as a means of transportation are increasingly becoming the flagship of the community. Along with the many flights today, aircraft are not spared also in carrying out maintenance. Punctuality and efficiency of work in maintenance are the main factors so that the aircraft can operate again on time, so that maintenance requires optimizing the number of mechanics according to the workload. While in fact there are still many treatments that are carried out not in accordance with the time that has been determined. This delay is very undesirable by both parties, because it will be detrimental in terms of time and cost. Therefore, careful aircraft maintenance planning and structured work lines must be carried out so that maintenance can be carried out as desired. The method used is the Critical Path Method (CPM), which is a network critical path method that uses linear time balance. Each activity can be completed faster than normal time by bypassing the activity for a certain fee. In the Critical Path Method (CPM) method, forward calculations and backward calculations are carried out so as to get the results of the critical path (slack). From the results of the analysis, it was found that the value of man hours needed was 89.52 man hours, while the value of man hours needed based on the company's calculation results was 97.43 man hours. There are differences in the results of man hours obtained by the author with from the company.